Design and Simulation of Cascaded Class-A Microwave Power Amplifier - Muhammad Faheem Siddique; Syed Haider Abbas; Hussnain Haider; Ali Bin Tahir (International Journal of Electrical and Computer Engineering (IJECE), 2013)
Microwave power amplifiers are the most significant components in wireless communications systems. As the technology continue to progress, the designers are facing new challenges and opportunities. The purpose of this work is to push the limits of efficiency and bandwidth of power amplifiers. The objective of this research is to design and build a prototype two stage Microwave power amplifier operated at 2.4 GHz with a linear region of operation up to our desired output of 0.5 watt or 27 dBm. The transistor used in the first stage is BFP540 while the output power of the first stage is the input of the second stage in which the ATF50189 transistor is used to for amplification. All the simulations and readings are taken by using AWR Microwave Office software. By using the load line Rl and the biasing points are achieved for both stages. The applications of our proposed device include many products in the field of microwave communications. One of the important applications of a Microwave power amplifier is in the output stage of a transmitter where a signal needs amplification before it is transmitted.DOI:http://dx.doi.org/10.11591/ijece.v3i5.3644